Analisis Pengembangan Wilayah Kabupaten Wonogiri Berbasis Sektor Unggulan Daerah - Saputra, Aditia Tunjung; Arif, Muhammad (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
The goal of this study was to identify the sectors that can be developed into leading sectors in Wonogiri Regency. This study used Shift Share analysis, Klassen Typology analysis, and location quotient analysis. The data used was the regional product gross of the Central Bureau of Statistics in 2015-2021. Based on the results of the LQ analysis, there were 11 leading industries, the highest of which were agriculture, forestry, and fisheries, with an LQ value of 2,282. The lowest value was for the water supply industry, with an LQ value of 1,059. There were six divisions in the non-basic sector. Based on the results of the Klassen Typology analysis, ten divisions were classified in the quadrant I category, three divisions were organized in the quadrant II category, five divisions were ranked in the quadrant III category, and three divisions were classified in the quadrant IV category. Finally, from the results of the Shift Share analysis, the growth component of the territory (N) was positive, the industrial structure component (M) was positive for 13 industries and negative for four drives, and the competitiveness component (C) was positive for 15 sectors and negative for four industries. The results of the analysis indicate that Wonogiri Regency has many senior officials.